Imidazoles and Quaternary Ammonium Compounds as Effective Therapies against (Multidrug-Resistant) Bacterial Wound Infections - Lauren Van de Vliet; Thijs Vackier; Karin Thevissen; David Decoster; Hans P. Steenackers (MDPI AG, 2024)
Background/Objectives: The rise and spread of antimicrobial resistance complicates the treatment of bacterial wound pathogens, further increasing the need for newer, effective therapies. Azoles such as miconazole have shown promise as antibacterial compounds; however, they are currently only used as antifungals. Previous research has shown that combining azoles with quaternary ammonium compounds yields synergistic activity against fungal pathogens, but the effect on bacterial pathogens has not been studied yet. Methods: In this study, the focus was on finding active synergistic combinations of imidazoles and quaternary ammonium compounds against (multidrug-resistant) bacterial pathogens through checkerboard assays. Experimental evolution in liquid culture was used to evaluate the possible emergence of resistance against the most active synergistic combination. Results: Several promising synergistic combinations were identified against an array of Gram-positive pathogens: miconazole/domiphen bromide, ketoconazole/domiphen bromide, clotrimazole/domiphen bromide, fluconazole/domiphen bromide and miconazole/benzalkonium chloride. Especially, miconazole with domiphen bromide exhibits potential, as it has activity at a low concentration against a broad range of pathogens and shows an absence of strong resistance development over 11 cycles of evolution. Conclusions: This study provides valuable insight into the possible combinations of imidazoles and quaternary ammonium compounds that could be repurposed for (topical) wound treatment. Miconazole with domiphen bromide shows the highest application potential as a possible future wound therapy. However, further research is needed into the mode of action of these compounds and their efficacy and toxicity in vivo.